Ternary cathode materials, preparation methods, screening methods, and secondary batteries
By forming a cladding layer in the range of 0.001 GPa/nm2 to 0.2 GPa/nm2 on the ternary positive electrode material particles, the problem of capacity loss and voltage attenuation during the cycling process is solved, and a ternary positive electrode material with high structural stability and cycling performance is achieved.
Patent Information
- Application Number
- CN202411719689.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The ternary cathode material has serious problems such as capacity loss, voltage attenuation and unsatisfactory performance during the cycle, which hinders its commercial application.
A ternary positive electrode material is used, and the particles include an active material matrix and a cladding layer. The cladding effective factor A is within the range of 0.001 GPa/nm2-0.2 GPa/nm2. A uniform cladding layer is formed by dry and wet coating to improve the structural stability and cyclic performance of the material.
The ternary positive electrode material has high structural stability, good circulation performance, low capacity attenuation rate and low residual alkali content, which has improved the overall performance of lithium-ion batteries.
Smart Images

Figure CN119208579B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary battery positive electrode materials, and in particular to a ternary positive electrode material, a preparation method, a screening method and a secondary battery. Background Art
[0002] Lithium nickel cobalt manganese oxide, a ternary cathode material for lithium-ion batteries, is considered to be the most likely cathode material for power batteries to be widely used because of its high discharge capacity, low production cost, stable layered structure, and good thermal stability. However, ternary cathode materials exhibit serious problems such as capacity loss, voltage decay, and unsatisfactory rate performance during the cycle process, which seriously hinders their commercial application.
[0003] According to existing research, the main reasons for capacity loss, voltage decay and poor rate performance include: some side reactions will occur when the positive electrode material is in direct contact with the electrolyte during the charge and discharge process, such as the dissolution of active materials and the decomposition of electrolyte on the surface of high oxidation state active materials; secondly, during the charge and discharge process, due to the repeated expansion and contraction of the crystal, cracks will appear between the primary particles, destroying the continuity between them and hindering electron transmission; when the electrolyte penetrates into the secondary particles through the microcracks, more serious side reactions will occur, and as the cut-off voltage increases, the microcracks will become more serious, resulting in an overly thick CEI film, reducing the interfacial activity and electrochemical properties of the material. At present, the industry widely adopts surface coating modification of ternary positive electrode materials to alleviate problems such as positive electrode / electrolyte interface reaction and intercrystalline cracking. Conventional chemical coating methods include: coprecipitation, sol-gel, hydrothermal and solid-state methods; traditional deposition methods include: spray drying, pulsed laser deposition, physical vapor deposition and chemical vapor deposition; advanced deposition methods include: atomic layer deposition and molecular layer deposition.
[0004] The existing coated and modified ternary positive electrode materials have poor stability and are still prone to material structure changes during use, causing capacity loss, voltage decay and poor rate performance of lithium-ion batteries.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a ternary positive electrode material, a preparation method, a screening method and a secondary battery, wherein the ternary positive electrode material has excellent structural stability and cyclability, and a low capacity decay rate.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a ternary positive electrode material, wherein the particles of the ternary positive electrode material include an active material matrix and a coating layer coated on the active material matrix, and the coating effective factor A of the ternary positive electrode material is 0.001 GPa / nm 2 -0.2GPa / nm 2 ,in, , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 .
[0009] In an optional embodiment, the 0.001-0.1, = , , where di 层厚 is the thickness of the coating layer of the ternary cathode material particles, in nm; di 内径 is the diameter of the active material matrix in the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles;
[0010] and / or, 160GPa-350GPa, among which , where N is the sample size of the ternary cathode material particles, E i is the Young’s modulus of the ternary cathode material particles measured by nanoindentation, in GPa;
[0011] and / or, 10nm 2 -3500nm 2 ,in , is the average thickness of the coating layer of the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles.
[0012] In an optional embodiment, the di 层厚 is 10nm-1000nm, the di 层厚 It is the average value of the sum of the thickness of the coating layer on the maximum Feret diameter and the sum of the thickness of the coating layer on the minimum Feret diameter of the ternary positive electrode material particles;
[0013] and / or, the di 内径 1μm-20μm, the di内径 It is the average of the active material matrix length at the maximum Feret diameter and the active material matrix length at the minimum Feret diameter of the ternary positive electrode material particles.
[0014] In an optional embodiment, the sample size N of the ternary positive electrode material particles is ≥10.
[0015] In an optional embodiment, the general formula of the active material matrix is Li x Ni a Co b M c M' 1-a-b-c A y O 2-y , wherein M is selected from at least one of Al and Mn; M' is selected from at least one of Zr, Sr, Mo, Ba, W, B, Ti, Mg, Li, C, Si, Ca, Cu, La, Ce, Bi, In, Nb and Y; A is selected from at least one of P and F; wherein 0.95≤x<1.1, a>0, b>0, c>0, 0.95≤(a+b+c)≤1, 0≤y≤0.01;
[0016] And / or, the coating layer is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2.
[0017] In a second aspect, the present invention provides a method for preparing the ternary cathode material according to any one of the aforementioned embodiments, comprising:
[0018] Pre-coating, using a first coating agent to dry-coat the active material matrix and perform a first calcination to obtain a pre-coated ternary positive electrode material;
[0019] Coating: wet coating the pre-coated ternary positive electrode material with a mixed coating agent and performing a second calcination to obtain the ternary positive electrode material.
[0020] In an optional embodiment, the preparation method satisfies at least one of the following features AF:
[0021] A. the first coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3, and MgF2;
[0022] B. The mass ratio of the first coating agent to the active material matrix is 0.05%-2%;
[0023] C. The first calcination temperature is 400°C-700°C, the atmosphere is oxygen, and the calcination time is 3h-10h;
[0024] D. The preparation of the active material matrix includes: calcining a mixture including a ternary positive electrode material precursor, a dopant and a lithium source, or a mixture including a ternary positive electrode material precursor and a lithium source to obtain the active material matrix.
[0025] E. The coating comprises: drying and granulating a slurry comprising a pre-coated ternary positive electrode material, a mixed coating agent and a solvent to obtain a powder, washing the powder, drying, second calcining and crushing the powder to obtain the ternary positive electrode material;
[0026] F. The second calcination temperature is 400℃-700℃, the atmosphere is oxygen, and the calcination time is 3h-10h;
[0027] In an optional embodiment, the coating satisfies at least one of the following characteristics ah:
[0028] a. The mass ratio of the mixed coating agent to the pre-coated ternary cathode material in the slurry is 5%-25%;
[0029] b. The mixed coating agent comprises a second coating agent and a surfactant, wherein the mass ratio of the mixed coating agent to the second coating agent is (15-25): 1;
[0030] c. The mixed coating agent comprises a second coating agent and a surfactant, wherein the surfactant is selected from at least one of sodium dodecylbenzene sulfonate, Tween-80, polymethacrylic acid, polyethylene glycol and ammonium polymethacrylate;
[0031] d. The mixed coating agent comprises a second coating agent and a surfactant, wherein the second coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, Mn3(PO4)2, AlPO4, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2;
[0032] e. The solid content of the slurry is 100g / L-200g / L;
[0033] f. The solvent is selected from at least one of methanol, ethanol, isopropanol and butanol;
[0034] g. The drying temperature is 60℃-200℃ and the drying time is 10h-25h;
[0035] h. The mixed coating agent is used to prepare the slurry after being subjected to air flow crushing, and the air flow crushing pressure is 5MPa-12MPa and the time is 2.5h-8h.
[0036] In a third aspect, the present invention provides a method for screening the ternary cathode material according to the aforementioned embodiment, wherein the ternary cathode material satisfies the following conditions:
[0037] ① The ternary positive electrode material comprises an active material matrix and a coating layer coated on the active material matrix;
[0038] ② The ternary cathode material meets the following requirements: the coating effective factor A is 0.001 GPa / nm 2 -0.2GPa / nm 2 ,in, , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 .
[0039] In a fourth aspect, the present invention provides a secondary battery, comprising the ternary positive electrode material described in any one of the aforementioned embodiments or the ternary positive electrode material prepared by the preparation method described in any one of the aforementioned embodiments.
[0040] The present invention has the following beneficial effects:
[0041] The coating effective factor A of the ternary cathode material in the present invention is 0.001 GPa / nm 2 -0.2GPa / nm 2 , the coating layer of the ternary cathode material and the active material matrix within this range meet , and Due to the coordinated relationship, the ternary positive electrode material has the characteristics of high structural stability, high cycle performance, low capacity decay rate and low residual alkali content. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0043] Figure 1 TEM image of the ternary cathode material prepared in Example 1;
[0044] Figure 2 This is the TEM image of the ternary positive electrode material prepared in Comparative Example 5. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0046] Among the existing coating modification methods, the solid phase method is the easiest method to achieve coating. It only requires mixing the coating material with the positive electrode material precursor and the lithium source or positive electrode powder, and then calcining to complete the coating, but the thickness and uniformity of the coating layer are difficult to control. The applicant found that the thickness and uniformity of the coating layer will affect its ability to resist stress changes during the contraction and expansion process of the active material during charging and discharging. At the same time, if the coating amount is small, the coating layer is poorly uniform, and the coating layer does not completely cover the active material, it will lead to exposure of the active material, resulting in its reaction with water and carbon dioxide in the air to form residual alkali during storage, and the electrolyte will be corroded during the charging and discharging process. Eventually, it will lead to changes in the material structure, causing capacity loss, voltage decay and poor rate performance of lithium-ion batteries.
[0047] An embodiment of the present invention provides a ternary positive electrode material, wherein the particles of the ternary positive electrode material include an active material matrix and a coating layer coated on the active material matrix, and the coating effective factor A of the ternary positive electrode material is 0.001 GPa / nm 2 -0.2GPa / nm 2 , specifically, it can be 0.001 GPa / nm 2 、0.002GPa / nm 2 、0.003GPa / nm 2 、0.005GPa / nm 2 、0.010GPa / nm 2 、0.020GPa / nm 2 、0.030GPa / nm 2 、0.050GPa / nm 2 、0.070GPa / nm 2 、0.090GPa / nm 2 、0.110GPa / nm 2 、0.130GPa / nm 2 、0.150GPa / nm 2 , 0.2GPa / nm 2 or 0.001GPa / nm 2 -0.2GPa / nm 2 Any value between , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 .
[0048] The coating layer of the ternary positive electrode material can serve as a protective layer to protect the ternary positive electrode material from being corroded by the electrolyte during the charge and discharge cycle, enhance the resistance of the ternary positive electrode material to H2O and CO2 in the surrounding air, and inhibit the generation of cracks due to the repeated expansion and contraction of the crystal during the charge and discharge process.
[0049] When the amount of coating material in the ternary positive electrode material is relatively large relative to the positive electrode material, but the coating layer is poorly uniform and has poor mechanical properties, the active material matrix may be exposed and the ternary positive electrode material may have poor structural stability; when the amount of coating material in the ternary positive electrode material is relatively small relative to the ternary positive electrode material, but the coating layer is well uniform and has excellent mechanical properties, the coating effectiveness may be high and the structural stability of the ternary positive electrode material may be high; when the amount of coating material in the ternary positive electrode material is relatively large relative to the positive electrode material, the active material is completely coated, and the mechanical properties are excellent, the coating layer may be too thick relative to the active material matrix, the coating uniformity is poor, and then the coating effectiveness is low and the structural stability of the ternary positive electrode material is poor. Therefore, it is necessary to combine the ratio of the coating layer thickness to the diameter of the active material matrix, the average Young's modulus, and the variance of the coating layer thickness to judge the structural stability of the ternary positive electrode material. Any one or two of them cannot indicate the structural stability of the ternary positive electrode material.
[0050] The coating effective factor A of the ternary cathode material in the present invention is 0.001 GPa / nm 2 -0.2GPa / nm 2 , within this range, it means that the coating layer of the ternary cathode material and the active material simultaneously meet , and The mutually coordinated relationship enables the positive electrode material to meet the coating effective factor and has the characteristics of high structural stability, high cycle performance, low capacity attenuation rate and low residual alkali content.
[0051] In some embodiments, the is 0.001-0.1, specifically, it can be 0.001, 0.003, 0.005, 0.007, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 or any value between 0.001-0.1, = , , where di 层厚 is the thickness of the coating layer of the ternary cathode material particles, in nm; di 内径 is the diameter of the active material matrix in the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles.
[0052] Due to d 层厚 It cannot reflect the relative relationship between the coating layer thickness and the particle size of the active material matrix in the ternary positive electrode material. Evaluate the relative relationship between the coating layer and the active material matrix in the ternary positive electrode material. The D value reflects the relative content of the coating layer and the active material matrix in the ternary positive electrode material. A too large value will reduce the proportion of active materials in the ternary positive electrode material. If the value is too small, the coating layer will not be able to fully protect the active material.
[0053] In some embodiments, the is 160 GPa-350 GPa, specifically, it can be 160 GPa, 170 GPa, 190 GPa, 210 GPa, 230 GPa, 250 GPa, 270 GPa, 290 GPa, 310 GPa, 330 GPa, 350 GPa or any value between 160 GPa-350 GPa, wherein , N is the sample size of the ternary cathode material particles, E i is the Young’s modulus of the ternary cathode material particles measured by nanoindentation, in GPa.
[0054] by Evaluate the mechanical properties of the ternary cathode material composed of the coating layer and the active material matrix. Under the premise of the same active material matrix, The size of is related to the type of coating agent, the thickness of the coating layer and the uniformity of the coating layer. The larger the Young's modulus of the selected coating agent, the higher the thickness of the coating layer and the higher the uniformity of the coating layer, the better the corresponding positive electrode material. The larger the positive electrode material, the The smaller the The coating layer of the ternary cathode material can inhibit the formation of microcracks and voids caused by stress changes in the active material matrix during the charge and discharge process. Specifically, the relationship between the force and the displacement of the indenter can be recorded by an atomic force microscope as the indenter slowly presses into the material surface, and the Young's modulus of the sample particles can be calculated by the system.
[0055] In some embodiments, the 10nm 2 -3500nm 2 , specifically, it can be 10nm 2 、30nm 2 , 50nm 2 , 100nm 2 、300nm 2 , 500nm 2 , 1000nm 2 , 1500nm 2 , 2000nm 2 , 2500nm 2 、3000nm 2 、3500nm 2 or 10nm 2 -3500nm 2 Any value between , is the average thickness of the coating layer of the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles.
[0056] by Evaluate the uniformity of the coating thickness of the positive electrode material. Since there is a difference in the uniformity of the coating layer when the coating amount and active material are equal, Indicates the uniformity of the coating on the surface of the active material. If part of the active material is exposed due to poor uniformity of the coating, the exposed part will form lithium-oxygen compounds during storage and circulation, and react with H2O and CO2 in the air to form residual alkali; the residual alkali will react with the electrolyte to form HF, and HF and Li2CO3 will react to generate CO2, causing the battery to swell and bloat, affecting its cycle performance and safety performance (potential danger of fire and explosion). HF will also dissolve the transition metal ions in the ternary positive electrode material NCM / NCA, destroy its layered crystal structure, and deteriorate the capacity retention rate of the electrode material. In addition, nickel-rich materials can react with electrolytes to generate byproducts that hinder lithium ion transmission and Ni-O-like resistance layers with rock salt structures, increasing diffusion internal resistance.
[0057] In some embodiments, the di 层厚 is 10 nm-1000 nm, specifically, can be 10 nm, 30 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm or any value between 10 nm and 1000 nm, the di 层厚 It is the average value of the sum of the thickness of the coating layer on the maximum Feret diameter and the sum of the thickness of the coating layer on the minimum Feret diameter of the ternary positive electrode material particles;
[0058] and / or, the di 内径 1 μm-20 μm, specifically, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or any value between 1 μm and 20 μm, wherein the di 内径 It is the average of the active material matrix length at the maximum Feret diameter and the active material matrix length at the minimum Feret diameter of the ternary positive electrode material particles.
[0059] In some embodiments, the maximum Feret's diameter and the minimum Feret's diameter are obtained by analyzing sample images using Matlab, and the length of the active material matrix and the thickness of the coating layer are obtained by analyzing sample images using ImageJ.
[0060] Specifically, after determining the maximum and minimum Feret diameters by Matlab analysis, the sample images were analyzed by ImageJ, and the thickness of the coating layer on the longest Feret diameter and the thickness of the coating layer on the shortest Feret diameter of the ternary positive electrode material were measured respectively. It should be noted that there were coating layers at both ends of the longest or shortest Feret diameter, and the thickness of the coating layers at both ends of the diameter were measured. Then, the sum of the thickness of the coating layers at both ends of the longest Feret diameter and the shortest Feret diameter was calculated respectively, and then the average of the sum of the thickness of the coating layers at both ends of the longest Feret diameter and the sum of the thickness of the coating layers at both ends of the shortest Feret diameter was calculated to obtain d 层厚 , and calculate its corresponding variance, we get ; Analyze the sample images with ImageJ, measure the average length of the active material matrix on the longest Feret diameter and the shortest Feret diameter of the ternary cathode material, and obtain d 内径 , , and then calculate the number of N positive electrode material particles The mean value of .
[0061] It should be noted that the sample image can be a TEM, SEM or other image that can show the thickness of the coating layer of the ternary positive electrode material and the size of the active material matrix.
[0062] In some embodiments, the number N of the ternary cathode material particles is ≥ 10. A larger sample size is more likely to capture the diversity of the population, which is conducive to reducing sampling errors. The samples selected when testing and calculating each parameter can be different, and the number of samples selected can be the same or different.
[0063] In some embodiments, the active material matrix has the general formula Li x Ni a Co b M c M' 1-a-b-c A y O 2-y , wherein M is selected from at least one of Al and Mn; M' is selected from at least one of Zr, Sr, Mo, Ba, W, B, Ti, Mg, Li, C, Si, Ca, Cu, La, Ce, Bi, In, Nb and Y; A is selected from at least one of P and F; wherein 0.95≤x<1.1, a>0, b>0, c>0, 0.95≤(a+b+c)≤1, 0≤y≤0.01;
[0064] And / or, the coating layer is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2.
[0065] The active material matrix can be doped with elements according to actual needs to improve certain performances of the prepared positive electrode material. Coating the active material matrix with oxides, fluorides or fast ion conductors is beneficial to improve the conductivity, cycle stability, etc. of the prepared ternary positive electrode material while isolating the active material matrix from the electrolyte.
[0066] An embodiment of the present invention provides a method for preparing the ternary positive electrode material according to any one of the aforementioned embodiments, comprising:
[0067] Pre-coating, using a first coating agent to dry-coat the active material matrix and perform a first calcination to obtain a pre-coated ternary positive electrode material;
[0068] Coating: wet coating the pre-coated ternary positive electrode material with a mixed coating agent and performing a second calcination to obtain the ternary positive electrode material.
[0069] A uniform coating layer is formed on the surface of the ternary cathode material by means of dry and wet secondary coating. The first coating is dry coating, which may specifically include: mixing the first coating agent, active material matrix and dispersant (such as water and ethanol, etc.) through ball milling, and then pre-coating the surface of the active material matrix. The pre-coating may not form a uniform coating layer, but when the subsequent secondary coating contacts with solvent and water, it can reduce the contact area between the active material matrix and the liquid to a certain extent, and can inhibit the deterioration of the material structure by water.
[0070] The pre-coated ternary cathode material is then coated for the second time by wet coating, which may specifically include: mixing a mixed coating agent, a pre-coated ternary cathode material and a solvent to obtain a slurry, so that the coating agent particles are deposited on the surface of the pre-coated ternary cathode material, so that it can make up for the defects of the first coating and achieve uniform coating, while increasing the structural stability of the coating layer and improving the uniformity of the coating layer, so that The uniform coating formed by the two coatings effectively isolates the active material matrix from the air, making it difficult for H2O and CO2 in the air to continue to react with the residual lithium on the surface to generate Li2CO3 or LiOH, inhibiting the side reactions at the cathode electrode / electrolyte interface and inhibiting Li +Large-scale loss can reduce the dissolution of transition metal ions, prevent the structural collapse of the ternary positive electrode material during the cycle, and improve the structural stability and cycle performance of the electrode material.
[0071] In some embodiments, the preparation method satisfies at least one of the following features AF:
[0072] A. the first coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3, and MgF2;
[0073] B. The mass ratio of the first coating agent to the active material matrix is 0.05%-2%, specifically, it can be 0.05%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.16%, 0.18%, 2% or any value between 0.05%-2%;
[0074] C. The first calcination temperature is 400°C-700°C, specifically, 400°C, 500°C, 600°C, 700°C or any value between 400°C-700°C, the atmosphere is oxygen, and the calcination time is 3h-10h, specifically, 3h, 4h, 6h, 8h, 10h or any value between 3h-10h;
[0075] D. The preparation of the active material matrix includes: calcining a mixture including a ternary positive electrode material precursor, a dopant and a lithium source, or a mixture including a ternary positive electrode material precursor and a lithium source to obtain the active material matrix.
[0076] E. The coating comprises: drying and granulating a slurry comprising a pre-coated ternary positive electrode material, a mixed coating agent and a solvent to obtain a powder; washing, drying, second calcining and crushing the powder to obtain the ternary positive electrode material;
[0077] F. The second calcination temperature is 400°C-700°C, specifically, it can be 400°C, 500°C, 600°C, 700°C or any value between 400°C and 700°C, the atmosphere is oxygen, and the calcination time is 3h-10h, specifically, it can be 3h, 4h, 6h, 8h, 10h or any value between 3h-10h.
[0078] Among them, since the uniformity of the coating layer obtained by dry coating is relatively poor, in order to avoid the defect of the uniformity of the coating layer obtained by the first coating cannot be compensated in wet coating, the dosage of the first coating agent should not be too much.
[0079] In some embodiments, the active material matrix can be selected from commercially available active materials or prepared according to the following method: mixing a ternary cathode material precursor, a dopant (if any), and a lithium source in a chemical formula ratio, ball milling at a rotation speed of 150 - 500 rpm for 1 - 10 h, and after uniform mixing, calcining at 700 - 1000 °C in an air or oxygen atmosphere for 15 - 30 h to obtain a nickel-cobalt-manganese ternary cathode material;
[0080] Among them, the elements of the dopant include at least one of Zr, Sr, Mo, Ba, W, B, Ti, Mg, Li, C, Si, Ca, Cu, La, Ce, Bi, In, Nb, Y, Al, Mn, P, and F. The doping can be an oxide, fluoride, carbonate, hydroxide, nitride, boride, nitrate of the corresponding doping element, or any combination thereof. The molar ratio of the doping substance to the precursor can be (0.01 - 0.05):1; the ternary cathode material precursor can be Ni x Co y Mn 1-x-y (OH)2, (0.25 < x < 0.9, 0 < y < 1, and x + y < 1); the lithium source can be at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, and their hydrates.
[0081] In some embodiments, the coating satisfies at least one of the following characteristics a - h:
[0082] a. The mass ratio of the mixed coating agent to the pre-coated ternary cathode material in the slurry is 5% - 25%. Specifically, it can be 5%, 10%, 15%, 20%, 25%, or any value between 5% - 25%;
[0083] b. The mixed coating agent includes a second coating agent and a surfactant, and the mass ratio of the surfactant to the second coating agent in the mixed coating agent is (15 - 25):1. Specifically, it can be 15:1, 17:1, 19:1, 21:1, 23:1, 25:1, or any value between (15 - 25):1;
[0084] c. The mixed coating agent includes a second coating agent and a surfactant, and the surfactant is selected from at least one of sodium dodecylbenzenesulfonate, Tween - 80, polymethacrylic acid, polyethylene glycol, and ammonium polymethacrylate;
[0085] d. The mixed coating agent comprises a second coating agent and a surfactant, wherein the second coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, Mn3(PO4)2, AlPO4, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2;
[0086] e. The solid content of the slurry is 100 g / L-200 g / L, specifically, it can be 100 g / L, 120 g / L, 140 g / L, 160 g / L, 180 g / L, 200 g / L or any value between 100 g / L and 200 g / L;
[0087] f. The solvent is selected from at least one of methanol, ethanol, isopropanol and butanol;
[0088] g. The drying temperature is 60 ℃-200 ℃, specifically, it can be 60 ℃, 100 ℃, 150 ℃, 200 ℃ or any value between 60 ℃-200 ℃, and the drying time is 10h-25h, specifically, it can be 10h, 15h, 20h, 25h or any value between 10h-25h;
[0089] h. The mixed coating agent is used to prepare the slurry after being subjected to air flow crushing, and the air flow crushing pressure is 5MPa-12MPa and the time is 2.5h-8h.
[0090] During the second coating, sufficient surfactant is introduced into the mixed coating agent to avoid polymerization of the second coating agent. At the same time, the mixed coating agent is subjected to air flow crushing before preparing the slurry, which can refine the mixed coating agent and make the two fully mixed, which is more conducive to avoiding agglomeration of the second coating agent and is conducive to uniform mixing of the second coating agent and the pre-coated ternary positive electrode material, so as to make up for the relatively poor uniformity of the coating layer during the first coating.
[0091] Among them, spray drying can be selected for drying and granulating the slurry to improve the sphericity of the powder. At the same time, the spray drying method can obtain relatively dense particles, which is beneficial to reduce the damage to the particles in the subsequent water washing step. Among them, the conditions for spray drying can be an inlet temperature of 200℃-260℃ and an outlet temperature of 100℃-210℃.
[0092] Since the ternary positive electrode material is prone to chemical de-lithiation reaction when in contact with water, resulting in deterioration of the material structure and electrochemical performance, the powder is washed with water after granulation in the present invention to wash away lithium oxide formed by roasting excess lithium source, and at the same time, the coating layer obtained by the previous pre-coating protects the positive electrode material, reduces the phenomenon of material structure deterioration caused by chemical de-lithiation caused by the water washing process, and effectively reduces the amount of residual lithium in the active material.
[0093] An embodiment of the present invention provides a method for screening the ternary cathode material described in the aforementioned embodiment, wherein the ternary cathode material satisfies the following conditions:
[0094] ① The ternary positive electrode material comprises an active material matrix and a coating layer coated on the active material matrix;
[0095] ② The ternary cathode material meets the following requirements: the coating effective factor A is 0.001 GPa / nm 2 -0.2GPa / nm 2 ,in, , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 .
[0096] The coating effective factor A of the ternary cathode material is 0.001GPa / nm 2 -0.2GPa / nm 2 The range indicates that the coating layer and active material of the ternary cathode material meet the requirements of , and The mutually coordinated relationship enables the positive electrode material to meet the coating effective factor and has the characteristics of high structural stability, high cycle performance, low capacity attenuation rate and low residual alkali content.
[0097] An embodiment of the present invention further provides a positive electrode plate, comprising the ternary positive electrode material described in the aforementioned embodiment or the ternary positive electrode material prepared by the method described in any one of the aforementioned embodiments.
[0098] An embodiment of the present invention provides a secondary battery, comprising the ternary positive electrode material described in any one of the aforementioned embodiments.
[0099] In the positive electrode sheet of the present invention, the positive electrode material layer generally comprises the positive electrode material, a binder and a conductive agent, and is generally formed by coating the positive electrode slurry, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode material, the conductive agent and the binder in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP).
[0100] In some optional embodiments, based on the total weight of the positive electrode material layer, the positive electrode material layer may contain 70wt%-97wt% of the ternary positive electrode material. Optionally, the weight proportion of the ternary positive electrode material in the positive electrode material layer is 85%-97%, 90%-97%, or 95%-97%. By adjusting the proportion of the ternary positive electrode material in the positive electrode material layer, the energy density and cycle life of the lithium-ion battery can be further improved.
[0101] In some embodiments, the binder of the positive electrode material layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and modified polymers thereof.
[0102] The conductive agent can improve the electronic conductivity of the positive electrode material layer. In some optional embodiments, the positive electrode material layer may contain 2wt%-20wt% of the conductive agent based on the total weight of the positive electrode material layer. Optionally, the weight proportion of the conductive agent in the positive electrode material layer is 2%-10%, or 2%-5%.
[0103] In some embodiments, the conductive agent of the positive electrode material layer may include one or more of superconducting carbon, carbon black (such as Super P, acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0104] The present invention provides a lithium-ion battery, comprising the positive electrode sheet described in the above embodiment, and also comprising a negative electrode sheet, an electrolyte and a separator.
[0105] [Negative electrode]
[0106] The negative electrode plate of the present invention comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector.
[0107] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is laminated on any one or both of the two opposite surfaces of the negative electrode current collector.
[0108] The negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting and collecting current. In some embodiments, the negative electrode current collector may be made of copper foil.
[0109] In the negative electrode sheet of the present invention, the negative electrode film layer generally comprises a negative electrode active material, a binder, a conductive agent and other optional additives. It is generally formed by coating a negative electrode slurry on a negative electrode current collector, drying and cold pressing. The negative electrode slurry is generally formed by dispersing a negative electrode positive electrode material, an optional conductive agent, an optional binder, an optional additive, etc. in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.
[0110] In some embodiments, the negative electrode active material may include one or more of artificial graphite, natural graphite, silicon-based materials, and tin-based materials. Alternatively, the negative electrode active material includes one or more of artificial graphite and natural graphite. Alternatively, the negative electrode active material includes artificial graphite.
[0111] In some embodiments, the conductive agent may include one or more of superconducting carbon, carbon black (eg, Super P, acetylene black, Ketjen black, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] In some embodiments, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0113] In some embodiments, other optional auxiliary agents include, for example, a thickener (eg, sodium carboxymethyl cellulose CMC-Na), a PTC thermistor material, and the like.
[0114] [Electrolytes]
[0115] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from an electrolyte. The electrolyte includes an electrolyte salt and a solvent.
[0116] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0117] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0118] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0119] [Isolation film]
[0120] The separator is disposed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The lithium ion battery of the present invention has no particular restrictions on the type of separator, and any known porous structure separator for lithium ion batteries can be selected. For example, the separator can be selected from one or more of a glass fiber film, a non-woven film, a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, and a multilayer composite film containing one or more of them.
[0121] The positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a lamination process or a winding process, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrode assembly is placed in an outer package, the electrolyte is injected and sealed, and a lithium-ion battery can be obtained.
[0122] The outer packaging of the lithium-ion battery is used to encapsulate the electrode assembly and the electrolyte. In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0123] The present invention has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square or any other shape.
[0124] In some embodiments, lithium-ion batteries may be assembled into a battery module. The battery module may contain multiple lithium-ion batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0125] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0126] The present invention also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack described in the present invention. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc. The device can select a secondary battery, a battery module or a battery pack according to its use requirements.
[0127] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0128] Embodiment 1:
[0129] This embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps:
[0130] The nickel cobalt manganese hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium carbonate were poured into a high-speed mixer and mixed, wherein the molar ratio of nickel-cobalt-manganese hydroxide precursor to lithium carbonate was 1:1.04. The mixture was mixed at a speed of 500 rpm for 5 minutes, and then stirred and dispersed at a speed of 1000 rpm for 15 minutes. After the materials were put into a bowl, the temperature was raised to 850°C in an oxygen atmosphere, kept at this temperature for 25 hours, and then cooled to room temperature. The materials were further crushed by a mechanical mill. The particle size D50 was controlled by the mechanical mill to be 9.3 μm, and a nickel-cobalt-manganese ternary positive electrode material was obtained.
[0131] A mixture containing nano-alumina, the obtained nickel-cobalt-manganese ternary positive electrode material and ethanol was mixed at a rotation speed of 500 rpm for 3 minutes, and then mixed at a rotation speed of 1000 rpm for 30 minutes to obtain a first mixture, wherein the mass of the nano-alumina was 0.2wt% of the obtained nickel-cobalt-manganese ternary positive electrode material, and the mass of the ethanol was 15wt% of the total mass of the nano-alumina and the obtained nickel-cobalt-manganese ternary positive electrode material. The first mixture was subjected to a secondary calcination treatment at a secondary calcination temperature of 500°C, an oxygen atmosphere for the secondary calcination, a heat preservation time of 6 hours, and a natural cooling to obtain a pre-coated ternary positive electrode material.
[0132] Sodium dodecylbenzene sulfonate and nano-alumina are mixed, wherein the mass ratio of the sodium dodecylbenzene sulfonate to the nano-alumina is 20:1, and a mixed coating agent is obtained after air flow crushing treatment, wherein the pressure of the air flow crushing is 8 MPa and the time is 4 hours.
[0133] The mixed coating agent, the pre-coated ternary positive electrode material and ethanol were mixed to form a slurry, which was stirred at a speed of 1000 rpm for 30 minutes, wherein the mixed coating agent was 10% of the mass of the pre-coated ternary positive electrode material, and the concentration of the slurry was 150 g / L. The powder was obtained after spray drying. The spray drying parameters were: the inlet temperature was 260°C, the outlet temperature was 120°C, the powder was washed twice with deionized water, dried at 100°C for 20 hours, and then calcined for the third time. The calcination was kept at 500°C for 8 hours in an oxygen atmosphere. The alumina-coated ternary positive electrode material was obtained after crushing. The TEM image is shown in FIG. Figure 1 , and obtain a coating layer with relatively uniform thickness.
[0134] Embodiment 2:
[0135] This embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps:
[0136] The nickel cobalt aluminum hydroxide precursor Ni 0.83 Co 0.15 Al 0.02 (OH)2 and lithium carbonate were poured into a high-speed mixer and mixed, wherein the molar ratio of nickel cobalt aluminum hydroxide precursor to lithium carbonate was 1:1.04. The mixture was mixed at a speed of 500 rpm for 5 minutes, and then stirred and dispersed at a speed of 1000 rpm for 15 minutes. After the materials were put into a bowl, the temperature was raised to 850°C in an oxygen atmosphere, kept at this temperature for 25 hours, and then cooled to room temperature. The materials were further crushed by a mechanical mill. The particle size D50 was controlled to be 15.0 μm by the mechanical mill to obtain a nickel cobalt aluminum ternary positive electrode material.
[0137] A mixture containing nano-alumina, the obtained nickel-cobalt-aluminum ternary positive electrode material and ethanol was mixed at a rotation speed of 500 rpm for 3 minutes, and then mixed at a rotation speed of 1000 rpm for 20 minutes to obtain a first mixture, wherein the mass of the nano-alumina was 0.05wt% of the obtained nickel-cobalt-aluminum ternary positive electrode material, and the mass of the ethanol was 15wt% of the total mass of the mixture of the nano-alumina and the obtained nickel-cobalt-aluminum ternary positive electrode material. The first mixture was subjected to a secondary calcination treatment at a temperature of 500°C, an oxygen atmosphere, a heat preservation time of 6 hours, and the pre-coated ternary positive electrode material was obtained by natural cooling.
[0138] Sodium dodecylbenzene sulfonate and nano-alumina are mixed, wherein the mass ratio of the sodium dodecylbenzene sulfonate to the nano-alumina is 25:1, and a mixed coating agent is obtained after air flow crushing treatment, wherein the air flow crushing pressure is 6 MPa and the time is 4 hours.
[0139] The mixed coating agent, pre-coated ternary positive electrode material and ethanol are mixed to form a slurry, which is stirred at a speed of 1000 rpm for 30 minutes, wherein the mixed coating agent is 8% of the mass of the pre-coated ternary positive electrode material, and the concentration of the slurry is 150 g / L. Powder is obtained after spray drying. The spray drying parameters are: inlet temperature is 220°C, outlet temperature is 210°C, and the powder is washed twice with deionized water and dried at 100°C for 20 hours. It is then calcined for the third time. The calcination is carried out at 500°C for 8 hours in an oxygen atmosphere. The alumina-coated ternary positive electrode material is obtained after crushing.
[0140] Embodiment 3:
[0141] This embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps:
[0142] The nickel cobalt manganese hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, lithium fluoride and lithium chloride are poured into a high-speed mixer and mixed, wherein the molar ratio of nickel cobalt manganese hydroxide precursor, lithium fluoride and lithium chloride is 1:1.02:0.04, mixed at a speed of 500 rpm for 5 minutes, and then stirred and dispersed at a speed of 1000 rpm for 15 minutes. After the materials are put into a bowl, the temperature is raised to 850°C in an oxygen atmosphere, kept warm for 25 hours, and then cooled to room temperature, and further crushed by a mechanical mill. The mechanical mill controls the particle size D50 to 10.1 μm to obtain a nickel cobalt manganese ternary positive electrode material.
[0143] A mixture containing nano titanium dioxide, the obtained nickel-cobalt-manganese ternary positive electrode material and ethanol was mixed at a rotation speed of 500 rpm for 3 minutes, and then mixed at a rotation speed of 1000 rpm for 30 minutes to obtain a first mixture, wherein the mass of the nano titanium dioxide was 0.05wt% of the obtained nickel-cobalt-manganese ternary positive electrode material, and the mass of the ethanol was 15wt% of the total mass of the nano titanium dioxide and the obtained nickel-cobalt-manganese ternary positive electrode material. The first mixture was subjected to a secondary calcination treatment at a secondary calcination temperature of 500°C, a holding time of 6 hours, an oxygen atmosphere, and the pre-coated ternary positive electrode material was obtained by natural cooling.
[0144] Sodium dodecylbenzene sulfonate and nano titanium dioxide are mixed, wherein the mass ratio of the sodium dodecylbenzene sulfonate to the nano titanium dioxide is 20:1, and a mixed coating agent is obtained after air flow crushing treatment, wherein the air flow crushing pressure is 9 MPa and the time is 3 hours.
[0145] The mixed coating agent, pre-coated ternary positive electrode material and ethanol are mixed to form a slurry, which is stirred at a speed of 1000 rpm for 30 minutes, wherein the mixed coating agent is 10% of the mass of the pre-coated ternary positive electrode material, and the concentration of the slurry is 150 g / L. Powder is obtained after spray drying. The spray drying parameters are: inlet temperature is 200°C, outlet temperature is 100°C, and the powder is washed twice with deionized water and dried at 100°C for 20 hours. It is then calcined for the third time. The calcination is kept at 500°C for 8 hours in an oxygen atmosphere. The nano-titanium dioxide-coated ternary positive electrode material is obtained after crushing.
[0146] The main differences between Examples 4-12 and Comparative Examples 1-2 relative to Example 1 are shown in Table 1. In addition to the differences in Table 1, Example 7 also has the following differences: both the first coating agent and the second coating agent are zinc oxide.
[0147] Table 1
[0148]
[0149] Comparative Example 3:
[0150] This embodiment provides a method for preparing a ternary positive electrode material, which is different from the embodiment 1 only in that water washing is performed when preparing the pre-coated ternary positive electrode material, and specifically includes the following steps:
[0151] The nickel cobalt manganese hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1(OH)2 and lithium carbonate were poured into a high-speed mixer and mixed, wherein the molar ratio of nickel-cobalt-manganese hydroxide precursor to lithium carbonate was 1:1.04. The mixture was mixed at a speed of 500 rpm for 5 minutes, and then stirred and dispersed at a speed of 1000 rpm for 15 minutes. After the materials were put into a bowl, the temperature was raised to 850°C in an oxygen atmosphere, kept at this temperature for 25 hours, and then cooled to room temperature. The materials were further crushed by a mechanical mill. The particle size D50 was controlled by the mechanical mill to be 9.3 μm, and a nickel-cobalt-manganese ternary positive electrode material was obtained.
[0152] A mixture containing nano-alumina, the obtained nickel-cobalt-manganese ternary positive electrode material and ethanol was mixed at a rotation speed of 500 rpm for 3 minutes, and then mixed at a rotation speed of 1000 rpm for 30 minutes to obtain a first mixture, wherein the mass of the nano-alumina was 0.2wt% of the obtained nickel-cobalt-manganese ternary positive electrode material, and the mass of the ethanol was 15wt% of the total mass of the nano-alumina and the obtained nickel-cobalt-manganese ternary positive electrode material. The first mixture was subjected to a secondary calcination treatment at a secondary calcination temperature of 500°C, an oxygen atmosphere, and a heat preservation time of 6 hours. After natural cooling, the mixture was washed twice with deionized water and dried at 100°C for 20 hours to obtain a pre-coated ternary positive electrode material.
[0153] Sodium dodecylbenzene sulfonate and nano-alumina are mixed, wherein the mass ratio of the sodium dodecylbenzene sulfonate to the nano-alumina is 20:1, and a mixed coating agent is obtained after air flow crushing treatment, wherein the pressure of the air flow crushing is 8 MPa and the time is 4 hours.
[0154] The mixed coating agent, pre-coated ternary positive electrode material and ethanol are mixed to form a slurry, which is stirred at a speed of 1000 rpm for 30 minutes, wherein the mixed coating agent is 10% of the mass of the pre-coated ternary positive electrode material, and the concentration of the slurry is 150 g / L. Powder is obtained after spray drying, and the spray drying parameters are: inlet temperature is 260°C, outlet temperature is 120°C, and the powder is calcined for the third time, and the calcination is kept at 500°C for 8 hours in an oxygen atmosphere, and the alumina-coated ternary positive electrode material is obtained after crushing.
[0155] Comparative Example 4:
[0156] This embodiment provides a method for preparing a ternary positive electrode material, which is different from the first embodiment in that no mixed coating agent is prepared, and sodium dodecylbenzene sulfonate and nano-alumina are directly mixed with the pre-coated ternary positive electrode material and the solvent to prepare a slurry, which specifically includes the following steps:
[0157] The nickel cobalt manganese hydroxide precursor Ni 0.8 Co 0.1 Mn 0.1(OH)2 and lithium carbonate were poured into a high-speed mixer and mixed, wherein the molar ratio of nickel-cobalt-manganese hydroxide precursor to lithium carbonate was 1:1.04. The mixture was mixed at a speed of 500 rpm for 5 minutes, and then stirred and dispersed at a speed of 1000 rpm for 15 minutes. After the materials were put into a bowl, the temperature was raised to 850°C in an oxygen atmosphere, kept at this temperature for 25 hours, and then cooled to room temperature. The materials were further crushed by a mechanical mill. The particle size D50 was controlled by the mechanical mill to be 9.3 μm, and a nickel-cobalt-manganese ternary positive electrode material was obtained.
[0158] A mixture containing nano-alumina, the obtained nickel-cobalt-manganese ternary positive electrode material and ethanol was mixed at a rotation speed of 500 rpm for 3 minutes, and then mixed at a rotation speed of 1000 rpm for 30 minutes to obtain a first mixture, wherein the mass of the nano-alumina was 0.2wt% of the obtained nickel-cobalt-manganese ternary positive electrode material, and the mass of the ethanol was 15wt% of the total mass of the nano-alumina and the obtained nickel-cobalt-manganese ternary positive electrode material. The first mixture was subjected to a secondary calcination treatment at a secondary calcination temperature of 500°C, an oxygen atmosphere, a heat preservation time of 6 hours, and the pre-coated ternary positive electrode material was obtained by natural cooling.
[0159] Nano-alumina, sodium dodecylbenzene sulfonate, pre-coated ternary cathode material and ethanol are mixed to form a slurry, and stirred at a speed of 1000rpm for 30min, wherein the total mass of nano-alumina and sodium dodecylbenzene sulfonate is 10% of the mass of the pre-coated ternary cathode material, the mass ratio of sodium dodecylbenzene sulfonate to nano-alumina is 20:1, the concentration of the slurry is 150g / L, and spray drying is performed. The spray drying parameters are: inlet temperature is 260°C, outlet temperature is 120°C, the powder is washed twice with deionized water, dried at 100°C for 20h, and then calcined for the third time. The calcination is kept at 500°C for 8h in an oxygen atmosphere, and the alumina-coated ternary cathode material is obtained after crushing.
[0160] Comparative Example 5:
[0161] This embodiment provides a method for preparing a ternary positive electrode material. The only difference from the embodiment 1 is that the total amount of nano-alumina is equal to that of the embodiment 1, and only one dry coating is performed. The TEM image is as follows: Figure 2 shown.
[0162] Comparative Example 6:
[0163] This embodiment provides a method for preparing a ternary positive electrode material, which is different from Embodiment 1 only in that the total amount of nano-alumina used is equal to that of Embodiment 1, and only one wet coating is performed.
[0164] The ternary cathode materials prepared in the above embodiments and comparative examples were tested, and the specific items and methods are as follows:
[0165] 1. Residual alkali test steps:
[0166] (1) Sample treatment: Weigh 10 g of sample into a 250 mL dry beaker, add 100 mL of pure water, add a stirring magnet into the beaker and cover with plastic wrap, stir with a magnetic stirrer for 30 min, let stand for 2 min after stirring, take a clean funnel and place it on a clean conical flask, fold the round filter paper in half and put it into the funnel for filtration, and cover the conical flask with a rubber cap after filtration; use hydrochloric acid as the titrant, and after the acid-base titration reaches the endpoint, determine the content of lithium hydroxide and lithium carbonate by the amount of hydrochloric acid used and the inflection point of the titration.
[0167] 2. Assembly of button battery:
[0168] In order to test the electrochemical properties of the material, the present invention makes a 2032-type button-type battery for various electrochemical performance tests. The specific steps of making the button-type battery are as follows: the preparation of the positive electrode sheet, first, the positive electrode material prepared in each embodiment and comparative example is placed in a vacuum oven at 85°C for 6 h, and then the active material, polytetrafluoroethylene and acetylene black are weighed in a mass ratio of 90:6:4, and added to the homogenizer at the same time, and a certain amount of N-methylpyrrolidone and zirconium beads are added at the same time, and the speed is 500 rpm for 5 min, and then the speed is 2000 rpm for 15 min to uniformly mix the binder, the conductive agent and the active material. The mixed slurry is evenly coated on a flat aluminum foil, and the coated electrode is placed in a vacuum constant temperature drying oven for 10 h, and the baking temperature is set to 120°C. After rolling and punching the dried electrode sheet, a positive electrode sheet with a diameter of 12 mm is obtained. Assemble CR2032 batteries in a glove box filled with argon gas, put the positive electrode sheet, negative electrode (lithium sheet), diaphragm and gasket into the battery shell respectively, add electrolyte and seal it to obtain the button battery to be tested.
[0169] The long cycle test conditions are as follows: window voltage is 3.0V and 4.3V, charge and discharge rate is 1C (1C=200 mA / g), and test temperature is 25°C.
[0170] 3. Young's modulus: observed with Bruker atomic force microscope, nanoindentation was tested in an argon-filled glove box using Keysight's Agilent NanoIndenter G200, and E was measured using the Berkovich indenter and Oliver Pharr method;
[0171] (1) For each batch of samples, 10 particles are randomly selected for testing and the average value is taken, which is the Young's modulus E of the material.
[0172] (2) Testing the Young's modulus of the sample after cycling: The cycled NMC electrode was taken out from the button cell, washed several times with dimethyl carbonate (DMC), and dried in a vacuum oven at room temperature overnight to obtain the test sample after cycling. Ten particles were randomly selected from each batch of samples for testing and the average value was taken.
[0173] (3) and : The TEM test images of the positive electrode materials obtained in each embodiment and comparative example were analyzed by using Matlab and ImageJ. Ten particles were randomly selected from each batch of samples and the and .
[0174] The above test results are shown in Table 2 and Table 3.
[0175] Table 2
[0176]
[0177] Table 3
[0178]
[0179] According to the data in Table 2 and Table 3, the positive electrode materials with the same chemical composition correspond to different , and The size of the coating effectiveness factor will be different, which will affect the physical and chemical properties of the positive electrode material. Specifically, within the specified parameter range, the larger the value of the coating effectiveness factor within the specified range, the better the electrochemical performance and / or cycle performance of the positive electrode material, and / or the lower the residual alkali on the surface of the positive electrode material. The specific reason is that the coating layer can effectively isolate the positive electrode material from the corrosion of water, carbon dioxide and electrolyte in the air during storage, and can resist the generation of cracks in the positive electrode material during charging and discharging. However, too high a layer thickness will not only reduce the proportion of active materials, but also increase the distance of lithium ion extraction / embedding process; similarly, too low and uneven layer thickness cannot play a good role in isolation and stress resistance.
[0180] It can be seen from Comparative Example 1 and Example 1 that for the same active material and active materials with similar particle diameters, the coating effective factors corresponding to different amounts of coating agents are very different, and the electrochemical properties of the corresponding battery materials are very different; it can be seen from Examples 1 to 7 that different , different Young's modulus, and 2 The final coating effective factors are very different, and the electrochemical performance is significantly different; compared with Example 1, although the coating effective factors of Examples 10-12 are within the preferred range, , and If any of the above items exceeds the preferred range, the electrochemical performance of the battery will be reduced. It can be seen from the comparison between Comparative Example 2 and Example 1 that , and Within the specified range, but when the coating effectiveness factor is outside the preferred range, the physical and chemical properties of the corresponding positive electrode material are significantly reduced. Therefore, by adjusting the ratio of the coating layer thickness to the active material matrix diameter , the ability to resist stress and coating uniformity , so that the coating effective factor is within the preferred range, and the physical and electrochemical properties of the obtained positive electrode material are better.
[0181] During the preparation process, water washing was performed after the first coating, as shown in Comparative Example 3, and the capacity retention rate was greatly reduced. The reason is that the first coating did not achieve comprehensive and uniform coating of the material, and there were exposed active material sites, and the active material was very sensitive to water. The material was more likely to undergo chemical de-Li reaction in water, resulting in deterioration of the material structure and electrochemical performance, reducing the capacity retention rate of the material and the E of the material before and after the cycle.
[0182] In the preparation process, the secondary coating agent and the surfactant are not mixed. As shown in Comparative Example 4, the E before and after the cycle are reduced compared with Example 1. The reason is that the failure to mix the secondary coating agent with the surfactant will lead to poor uniformity of the coating layer on the surface of the material, resulting in a decrease in the E of the material. The capacity retention rate of the material in Comparative Example 4 is not as good as that in Example 1.
[0183] The coating obtained by dry coating has poor uniformity, such as Figure 1 and Figure 2 As shown, the coating uniformity of Comparative Example 5 is poor compared to Example 1, which will lead to a decrease in the E of the material, causing the active material to react with water and carbon dioxide in the air during storage, and the exposed active material will also react with the electrolyte during the cycle, causing damage to the positive electrode material. The final manifestation is the accumulation of stress damage caused by shrinkage / expansion during the electrochemical cycle, which greatly reduces the E after the cycle.
[0184] However, if only wet coating is used in the preparation process, it will also cause the nanoparticles of the coating agent to agglomerate and form large particle coating. Therefore, only dry coating or wet coating will reduce the uniformity of the coating. For Comparative Examples 5 and 6, the material capacity retention rate and the E of the material before and after the cycle are lower than those in Example 1.
[0185] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ternary positive electrode material, characterized in that: The particles of the ternary positive electrode material include an active material matrix and a coating layer coated on the active material matrix, and the coating effective factor A of the ternary positive electrode material is 0.001 GPa / nm 2 -0.2GPa / nm 2 ,in, , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 ; The coating layer is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2; Said 0.001-0.1, = , , where di 层厚 is the thickness of the coating layer of the ternary cathode material particles, in nm; di 内径 is the diameter of the active material matrix in the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles; the di 层厚 is 10nm-1000nm, the di 层厚 is the average value of the sum of the thickness of the coating layer on the maximum Feret diameter and the sum of the thickness of the coating layer on the minimum Feret diameter of the ternary positive electrode material particles; the di 内径 1μm-20μm, the di 内径 is the average of the active material matrix length on the maximum Feret diameter and the active material matrix length on the minimum Feret diameter of the ternary positive electrode material particles; Said 160GPa-350GPa, among which , where N is the sample size of the ternary cathode material particles, E i is the Young’s modulus of the ternary cathode material particles measured by nanoindentation, in GPa; Said 10nm 2 -3500nm 2 ,in , is the average thickness of the coating layer of the ternary positive electrode material particles, in nm; N is the sample size of the ternary positive electrode material particles.
2. The ternary cathode material according to claim 1, characterized in that: The sample size N of the ternary positive electrode material particles is ≥10.
3. The ternary cathode material according to claim 1, characterized in that: The general formula of the active material matrix is Li x Ni a Co b M c M' 1-a-b-c A y O 2-y , wherein M is selected from at least one of Al and Mn; M' is selected from at least one of Zr, Sr, Mo, Ba, W, B, Ti, Mg, Li, C, Si, Ca, Cu, La, Ce, Bi, In, Nb and Y; A is selected from at least one of P and F; wherein 0.95≤x<1.1, a>0, b>0, c>0, 0.95≤(a+b+c)≤1, 0≤y≤0.
01.
4. A method for preparing the ternary positive electrode material according to any one of claims 1 to 3, characterized in that: include: Pre-coating, using a first coating agent to dry-coat the active material matrix and perform a first calcination to obtain a pre-coated ternary positive electrode material; The mass ratio of the first coating agent to the active material matrix is 0.05%-2%; Coating, using a mixed coating agent to wet-coat the pre-coated ternary positive electrode material and perform a second calcination to obtain the ternary positive electrode material; drying and granulating a slurry including the pre-coated ternary positive electrode material, the mixed coating agent and the solvent to obtain a powder, washing the powder with water, drying, a second calcination and crushing to obtain the ternary positive electrode material; the mass ratio of the mixed coating agent to the pre-coated ternary positive electrode material in the slurry is 5%-25%; the mixed coating agent includes a second coating agent and a surfactant, and the mass ratio of the surfactant to the second coating agent in the mixed coating agent is (15-25):
1.
5. The method for preparing the ternary cathode material according to claim 4, characterized in that: The preparation method satisfies at least one of the following features AD: A. the first coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3, and MgF2; B. The first calcination temperature is 400℃-700℃, the atmosphere is oxygen, and the calcination time is 3h-10h; C. The preparation of the active material matrix comprises: calcining a mixture comprising a ternary positive electrode material precursor, a dopant and a lithium source or a mixture comprising a ternary positive electrode material precursor and a lithium source to obtain the active material matrix; D. The second calcination temperature is 400℃-700℃, the atmosphere is oxygen, and the calcination time is 3h-10h.
6. The method for preparing the ternary cathode material according to claim 5, characterized in that: The coating satisfies at least one of the following features af: a. The mixed coating agent comprises a second coating agent and a surfactant, wherein the surfactant is selected from at least one of sodium dodecylbenzene sulfonate, Tween-80, polymethacrylic acid, polyethylene glycol and ammonium polymethacrylate; b. The mixed coating agent comprises a second coating agent and a surfactant, wherein the second coating agent is selected from at least one of V2O5, Al2O3, ZrO2, TiO2, SnO2, ZnO, MgO, RuO2, La2O3, Mn3(PO4)2, AlPO4, CeO2, Co3O4, SiO2, FePO4, Li3PO4, Li2MnO3, LiAlO2, Li2TiO3, Li2ZrO3, Li3VO4, Li2SiO3, AlF3, LaF3 and MgF2; c. The solid content of the slurry is 100g / L-200g / L; d. The solvent is selected from at least one of methanol, ethanol, isopropanol and butanol; e. The drying temperature is 60℃-200℃ and the drying time is 10h-25h; f. The mixed coating agent is used to prepare the slurry after being crushed by air flow, and the air flow crushing pressure is 5MPa-12MPa and the time is 2.5h-8h.
7. A method for screening the ternary cathode material according to claim 1, characterized in that: The ternary cathode material meets the following conditions: ① The ternary positive electrode material comprises an active material matrix and a coating layer coated on the active material matrix; ② The ternary cathode material meets the following requirements: the coating effective factor A is 0.001 GPa / nm 2 -0.2GPa / nm 2 ,in, , is the average value of the ratio of the coating thickness of the ternary positive electrode material particles to the diameter of the active material matrix, No units; is the average Young's modulus of the ternary cathode material particles, The unit is GPa; is the variance of the coating thickness of the ternary cathode material particles, The unit is nm 2 .
8. A secondary battery, characterized in that: It includes the ternary positive electrode material described in any one of claims 1-3 or the ternary positive electrode material prepared by the preparation method described in any one of claims 4-6.
Citation Information
Patent Citations
Positive electrode active material, preparation method thereof, positive electrode plate and lithium ion secondary battery
CN112447951A
Cited By
Ternary positive electrode material, preparation method, screening method and secondary battery
EP4787474A1